2017
DOI: 10.1002/suco.201700128
|View full text |Cite
|
Sign up to set email alerts
|

Stage of construction: An essential consideration in designing reinforced concrete building structures

Abstract: This paper analyzes the potential influence of the construction process on the serviceability stage of the structure of reinforced concrete (RC) buildings. For this, a number of cases of buildings erected by habitual construction processes were simulated by a finite elements model, including and excluding the construction process. The shoring–clearing–striking method was seen the least harmful to the long‐term behavior, but even so maximum loads during construction exceeded the design loads. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Apart from the numerical studies described in Section 5. [92,93], Kang et al [94], Hwang et al [95] and Alvarado et al [96,97]) confirmed the conclusions reached and emphasised the importance of reducing cracking and the loads on slabs under construction.…”
Section: Creep and Shrinkage Effects On Load Transmissionmentioning
confidence: 72%
“…Apart from the numerical studies described in Section 5. [92,93], Kang et al [94], Hwang et al [95] and Alvarado et al [96,97]) confirmed the conclusions reached and emphasised the importance of reducing cracking and the loads on slabs under construction.…”
Section: Creep and Shrinkage Effects On Load Transmissionmentioning
confidence: 72%
“…In the equation (10), we set A 1 as the area of distributed reinforcement parallel to the truss bar within the range of slab width F and set β 1 as the ratio of the elastic modulus of the reinforcement in the composite beam to the concrete of the composite slab, and t is the thickness of the composite slab. rough equation (10), the automatic detection of component design results is completed.…”
Section: Calculation Of Bearing Capacity and Test Equationmentioning
confidence: 99%
“…Second, there is no standardized and uniform information standard in the eld of architecture, which makes it impossible to realize information integration and sharing among di erent application systems [8]. In the design of the projects, construction operation, maintenance of engineering projects, utilization of natural resources, usage of eco-friendly materials, and sustainable energy play important role [9][10][11]. erefore, the project developers attempt to use newer technologies, which are environment friendly and can certainly add the factor of sustainable energy for impacting the environment positively.…”
Section: Introductionmentioning
confidence: 99%
“…Für die Weiterentwicklung der Berechnungen hin zu ganzheitlichen 3D‐Gebäudemodellen müssen die Auswirkungen jedoch detaillierter erfasst werden. In [10] wurde dafür eine sehr detaillierte Abbildung gewählt, bei der die Schalung und die Unterstellungen mitmodelliert werden. Dabei wurden auch unterschiedliche Reihenfolgen und Zeitpunkte des Entfernens der Schalung sowie der Unterstellung untersucht.…”
Section: Bauprozessmodellierungunclassified